Diagnostic yield of combined ultrasound-guided fine needle aspiration and core needle biopsy versus either technique alone in peripheral lung and pleural lesions - Rania Ahmed Sweed; Yehia Mohamed Khalil; Hany Amin Sharawy; Eman Sheta Ali Gawdat Alsawy; Mina Botros (The Egyptian Journal of Bronchology, 2023)
Abstract Introduction Ultrasound (US) has become an integral tool for chest assessment as it provides crucial information on pleural pathologies and peripherally located lung lesions. Aim To assess the diagnostic yield of combined fine needle aspiration (FNAB) and core needle biopsy (CNB) versus each technique ultrasound-guided in peripheral lung and pleural lesions. Methodology The present study enrolled 30 patients presenting to Alexandria Main University Hospital, with CT scans showing undiagnosed peripheral lung or parietal pleural lesions with or without effusion. A full ultrasound chest assessment was done covering 12 regions. Assessment of the lesion of interest, vascularity was assessed via color Doppler, locating the safest entry site. Real-time US-guided FNAB was done using a spinal needle 22 gauge. Then real-time US-guided CNB using 18 gauge Trucut needle in the same setting. Duration and complications of each procedure were reported. In FNAB, three smears were prepared, fixed in alcohol, and stained with hematoxylin and eosin stain. The remaining sample was fixed in formalin and centrifuged to prepare cell blocks. On the other hand, Trucut needle biopsy specimens were fixed in formalin and processed as paraffin-embedded blocks. Immunohistochemical staining was done. The results were classified into four categories (inadequate, negative, suspicious, and positive for malignancy. Results The diagnostic yield of combined techniques was 96.7% versus 63.3% using FNAB and 96.7% using CNB. The sensitivity of FNAB was 86% while CNB was 95%. The specificity and positive predictive value of both methods were 100%. The negative predictive value of FNAB was 57% versus 80% for CNB in peripheral lung lesions. Duration of US-guided CNB was statistically significantly longer than that of FNAB in both peripheral lung and pleural lesions. No major complications were reported using either technique. Conclusion Combined FNAB and CNB were not superior to CNB alone regarding diagnostic yield but were superior to FNAB. Ultrasound-guided CNB has a superior diagnostic yield over FNAB, with no statistically significant difference regarding associated complications, both techniques are safe. FNAB provided sufficient material for ancillary molecular testing.